1978
DOI: 10.1128/jb.136.2.815-817.1978
|View full text |Cite
|
Sign up to set email alerts
|

Thermal adaptation in yeast: obligate psychrophiles are obligate aerobes, and obligate thermophiles are facultative anaerobes

Abstract: The obligate psychrophilic yeasts Torulopsis psychrophila, T. austromarina, Leucosporidium frigidum, L. gelidum, and L. nivalis were obligate aerobes and were unable to grow anaerobically. In contrast, the obligate thermophilic yeasts T. bovina, T. pintolopesii, Candida slooffii, and Saccharomyces telluris were facultative anaerobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Contrary to previous studies and to our expectation, our ITS-BLAST result showed that we isolated C. psychrophila, a psychrophilic yeast, through our standard enrichment protocol where we incubated all the yeasts at 30°C for 2 days. This is interesting considering one of the defining features of psychrophilic yeast is that they cannot grow well beyond an upper limit temperature of 20°C (Watson et al, 1978). However, this finding might be an Yeast diversity from city tree hollows artifact related to misidentification in the GenBank and/ or the lack of ITS sequence variation among closely related species (Nilsson et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to previous studies and to our expectation, our ITS-BLAST result showed that we isolated C. psychrophila, a psychrophilic yeast, through our standard enrichment protocol where we incubated all the yeasts at 30°C for 2 days. This is interesting considering one of the defining features of psychrophilic yeast is that they cannot grow well beyond an upper limit temperature of 20°C (Watson et al, 1978). However, this finding might be an Yeast diversity from city tree hollows artifact related to misidentification in the GenBank and/ or the lack of ITS sequence variation among closely related species (Nilsson et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Later studies showed its affiliation with the genus Debaryomyces belonging to the CTG clade of Saccharomycotina ( 2 , 3 ). C. psychrophila is an obligate aerobe and psychrophile that does not grow at temperatures above 17°C ( 4 ). Its adaptation to cold environments is mediated by lipidome enrichment for unsaturated fatty acyl moieties ( 5 , 6 ) and stress proteins, which are induced at a mild heat shock (25°C) ( 7 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The observations were surprising since alcoholic fermentation is often performed under anaerobic conditions or low dissolved oxygen conditions [46,47]. Consequently, yeast performance was expected to also be negatively affected by HA, albeit that yeasts are generally characterized as facultative anaerobes and some yeasts can still survive or grow under aerobic conditions [48,49,50,51]. Since only air (with 21% oxygen) was used, it was also plausible that different alcohol consumption profiles could have been observed if technical grade oxygen was tested—a condition that can exacerbate hyperoxia.…”
Section: Resultsmentioning
confidence: 99%